Resource use and food self-sufficiency at farm scale within two agro-ecological zones of Rwanda - Bucagu, C.; Vanlauwe, Bernard; Wijk, Mark T. van; Giller, Kenneth E. (Springer, 2014)
Resource use and management are major determinants of the food self-sufficiency of smallholder farmers in sub-Saharan Africa. A study was conducted in Rwanda in two contrasting agro-ecological zones (Central plateau and Buberuka) to characterise farms, quantify their resource flows, and evaluate the effect of resource management on food self-sufficiency. The Simbi and Kageyo sectors were selected as the representatives of agro-ecological zones and two villages were selected within each sector. Wealth ranking, focus group discussions and formal survey techniques were used. Farms were classified into resource groups (RGs) that differed with regards to socio-economic and food self-sufficiency status. Soils were more fertile in Kageyo (Buberuka) than in Simbi (Central plateau). In both sites 67 % or more of the households were classified in the poorest category who cultivated less than 0.2 ha and experienced 4–5 months of food deficit each year. The partial N balance was more negative in Kageyo (−35.87 kg N ha−1 year−1) while the P balance was negative in close fields and outfields but positive in homefields (0.43 kg P ha−1 year−1). Calorie and protein availability were insufficient in RG1 (poor resource group) and RG2 (moderate resource group) farms in Simbi and RG1 (poor resource group) in Kageyo. Boundary line analysis indicated that poor soil C contents led to 0.6–0.8 t ha−1 less yield with respect to the attainable yield in better fields in RG 2. Closing the maize yield gap would result in doubling the energy and protein intake in Simbi. In such complex agricultural systems, there is a need to apply an integrated and multi-dimensional approach to understand differences among farms, identify limitations to food production and explore realistic options to ensure sustainable agricultural production and food self-sufficiency.